Effect of Combined Application of Desulfurization Gypsum and Soil Amendment KIA on Saline-Alkali Soil Improvement - Qinghong Xiao; Wei Wei; Hao Wu; Kunyue Wu; Xue Gong; Meng Li; Shiwen Wang; Lina Yin (Agronomy)
Saline-alkali soil imposes severe adverse effects on soil utilization and agriculture production worldwide. Amelioration of saline-alkali soil is crucial to ensure global food security and promote sustainable agricultural development. Here, the effects of the combined application of soil amendment desulfurization gypsum (G) and KIA (K, an industrial organic by-product) on soil improvement and plant growth were investigated. Two experiments, a soil column leaching test and a pot experiment for plant growth, were carried out. The results showed that the combined application of G and K reduced soil pH significantly. Although the soil Na+ contents had no change in the combined treatments, the K+, Ca2+ and Mg2+ contents were significantly higher, and the HCO3− and Cl− contents were significantly lower, compared to the control. Furthermore, maize plants exhibited a higher photosynthetic rate and greater dry weight in the combined treatments. Additionally, after plant growth, the soil enzyme activities increased. These results showed that the combined application of G and K could have a more favorable impact on soil improvement by reducing soil pH, enhancing soil ion exchange, increasing soil nutrient contents, and promoting plant growth. Our study suggests that KIA is an effective and eco-friendly soil amendment for improving saline-alkali soil.